Seismic Stiffness Evaluation of RC Dual Systems in Varying Geometries: A Pushover-Based Study Using Indonesian Codes - Fuqaha, Sameh; Nugroho , Guntur (Jurnal Teknik Sipil dan Perencanaan, 2025)
This study evaluates the seismic performance of reinforced concrete (RC) dual systems that combine moment-resisting frames with shear walls, using nonlinear pushover analysis in accordance with Indonesian seismic design codes (SNI 1726:2019 and SNI 2847:2019). A total of 32 analytical models were developed to examine the influence of four critical parameters: story height (3–10 stories), span length (5.5–6.5 m), shear wall thickness (200–250 mm), and concrete compressive strength (20–25 MPa). The elastic stiffness factor was determined as the base shear ratio to roof displacement at the onset of first hinge formation. In contrast, base shear capacity was derived from the pushover curves. Results show that geometric parameters exert the most decisive influence on seismic response, with stiffness decreasing by more than 50 percent as story height increases and by approximately 8 percent with longer spans. Material enhancements provide only modest gains of 2 to 7 percent. These findings emphasize the dominant role of structural configuration in drift control and ductility demand, offering practical recommendations for optimizing RC dual systems under Indonesian codes and improving the resilience of mid- to high-rise buildings in seismic regions.